A Critical Analysis of the Implementation Process of Education Policy Borrowing: New Curriculum Reform in China (Asian Education Studies, 2022)
Through the current education reform in mainland China, namely the ―new curriculum reform‖ (NCR), this paper examines the situation of education policy reference. New curriculum reform, namely ―a new round of basic education curriculum reform‖. Alternative approaches, such as school-based curricula, student-centred teaching methods, and formative assessment, have been used to draw on the NCR. In this essay, the borrowing process of China‘s new curriculum reform will be analysed and discussed based on the four-stage analysis of Phillips and Ochs. At the same time, it focuses on the analysis of the core content—the specific implementation process of NCR, especially the content of ―student-centred‖ pedagogy.